An evaluation of the nomina for death adders (Acanthophis Daudin, 1803) proposed by Wells & Wellington (1985), and confirmation of A. cryptamydros Maddock et al., 2015 as the valid name for the Kimberley death adder - Ellis, Ryan J.; Kaiser, Hinrich; Maddock, Simon T.; Doughty, Paul; Wüster, Wolfgang (Zootaxa, 2021)
We assess the availability of four names proposed by Wells & Wellington (1985) for Australian death adders (Acanthophis). In agreement with previous literature, A. hawkei is an available name, whereas A. armstrongi, A. lancasteri, and A. schistos are not described in conformity with the requirements of Articles 13.1.1 or 13.1.2 of the International Code of Zoological Nomenclature and are therefore considered nomina nuda. Consequently, A. cryptamydros Maddock et al., 2015, is confirmed as the valid name for the Kimberley death adder of Western Australia. We comment on the need for greater clarity in the Code, and emphasise that the responsibility for establishing the availability of new nomina rests with their authors, not subsequent researchers.